2019
DOI: 10.1152/japplphysiol.00199.2016
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ventricular hypertrophy and myocardial mechanics in physiological and pathological hypertrophy

Abstract: LEFT VENTRICULAR HYPERTROPHY (LVH) is an adaptive response to physiologic or pathologic stimuli and distinguishing between the two has obvious clinical implications. However, asymmetric septal hypertrophy and preserved cardiac function are noted in early stages in both cases. We characterized the early anatomic and functional changes in a mouse model of physiologic and pathologic stress using serial echocardiography-based morphometry and tissue velocity imaging. Weight-matched CF-1 male mice were separated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
3
20
0
1
Order By: Relevance
“…Furthermore, we needed to document this finding prospectively beyond the cross-sectional observations in humans and studied the evolution of segmental remodeling in an animal model using third-generation microscopic ultrasonography. 9 , 10) In this study, BS hypertrophy was the initial remodeling in animals with mechanic blockage by transaortic construction which is a completely consistent finding with BS hypertrophy in the patients with aortic stenosis. 1) …”
supporting
confidence: 83%
“…Furthermore, we needed to document this finding prospectively beyond the cross-sectional observations in humans and studied the evolution of segmental remodeling in an animal model using third-generation microscopic ultrasonography. 9 , 10) In this study, BS hypertrophy was the initial remodeling in animals with mechanic blockage by transaortic construction which is a completely consistent finding with BS hypertrophy in the patients with aortic stenosis. 1) …”
supporting
confidence: 83%
“… 19 , 20 The volume overload is significantly higher than normal. 21 In the present study, it was found that EL-B, EL-M and EL-A during the P1, P2 and P3 were significantly higher in the NLVH group than in the control group. Before LVH formation in patients with HTN, the LV has an increased extracellular matrix, reduced elasticity and active relaxation capacity, increased diastolic pressure in the cardiac chambers, increased pressure load on the inner myocardium compared with the outer myocardium, weakened longitudinal contraction, and uncoordinated contraction of the inner and outer myocardium, causing the abnormal formation of cardiac chamber blood flow vortex.…”
Section: Discussionsupporting
confidence: 48%
“…Studies exploring the effects of exercise on cardiac size and left ventricular function have demonstrated that exercise caused an increase in cardiac size and improvement in left ventricular diastolic function, which is physiological, rather than pathological, hypertrophy 76 . Physiological hypertrophy is a typical manifestation of the cardioprotective effects of exercise, quite different from pathologic hypertrophy 77 , 78 . The serum level of natriuretic peptides (N-terminal proatrial and probrain natriuretic peptide) are biomarkers, which allow differentiation between physiological and pathologic cardiac hypertrophy 79 .…”
Section: The Mechanism Of Exercise-induced Cardiac Protectionmentioning
confidence: 99%